Teachers as Agents of Religious Moderation: Insights from Indonesia as a Multicultural Country - Ade Husna; Andar Nubowo; Yamudin Salaeh (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
This study explores the role of teachers from diverse religious backgrounds in promoting religious moderation and tolerance in Indonesia, a nation characterized by its multicultural and multi-religious composition. Drawing on qualitative research methods, the study examines how teachers' personal beliefs, professional practices, and educational frameworks contribute to fostering interreligious harmony and peaceful coexistence. The research highlights the importance of religious moderation, particularly in the context of Indonesia's educational system, which emphasizes tolerance as part of national policy. By analyzing the perspectives and strategies employed by Islamic, Christian, Catholic, Hindu, Buddhist, and Confucian educators, the paper identifies key practices and challenges in cultivating inclusivity within classrooms and communities. The findings underscore the critical role of teachers as moral role models and agents of societal change, offering valuable insights for policymakers and practitioners aiming to advance harmony in Indonesia's pluralistic society. This research has significant implications for educational policy and curriculum development, suggesting that integrating structured interfaith dialogue, values-based education, and teacher training programs can further strengthen religious moderation efforts. Additionally, it provides a framework for other multicultural societies seeking to implement effective strategies for fostering tolerance and reducing sectarian divides through education.Keywords: religious moderation, tolerance, education, multicultural society